A method for preparing carbon nanofibers reinforced by ionization pretreatment

The PAN nanofibers are modified by alkali hydrolysis, which solves the structural defects and high cost problems caused by the stabilization cyclization reaction in the preparation of traditional carbon nanofibers, and achieves the efficient preparation of high-strength carbon nanofibers.

CN118223155BActive Publication Date: 2024-12-31DONGHUA UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410439679.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2024-12-31
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

In the preparation of traditional carbon nanofibers, the stabilization cyclization reaction leads to structural defects and high costs, making it difficult to effectively prepare high-strength carbon nanofibers.

Method used

The PAN nanofibers are modified in situ by alkali hydrolysis to introduce ionic groups, promoting carbon chain cyclization, improving the formation efficiency of the stable structure, and avoiding the damage of the precursor structure.

Benefits of technology

The mechanical strength of carbon nanofibers is effectively improved and economically avoided structural defects and high cost problems in traditional methods, and carbon nanofibers with higher mechanical properties are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118223155B_ABST
    Figure CN118223155B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing carbon nanofibers enhanced by ionization pretreatment. The stabilization process is a key step in producing polyacrylonitrile-based carbon nanofiber materials. The present invention can optimize the reaction process of the stabilization treatment step by introducing ionic groups, promote carbon chain cyclization, and improve the performance of carbon nanofibers. Different from the traditional method of treating the precursor polymer before spinning, the present invention performs ionization treatment on the nanofibers after spinning, which can not only reduce the damage to the polymer structure, but also effectively introduce carboxylate ion groups. Finally, high-strength carbon nanofibers were obtained by the method of the present invention, and the mechanical strength was found to reach 70.4MPa after testing. Therefore, the method of the present invention can efficiently and simply prepare high-strength carbon nanofibers, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of carbon nanofibers reinforced by ionization pretreatment, belonging to the technical field of carbon nanofiber membranes. Background Art

[0002] Carbon nanofiber is a new type of nano inorganic fiber material with a carbon content of 90% or more. It has the advantages of high specific strength, low density, ultra-high specific surface area, compact structure, corrosion resistance, etc. It has broad application prospects in the fields of catalysts, separation materials, etc. Chemical deposition and electrospinning are two common methods for preparing carbon nanofibers. Chemical deposition can prepare carbon nanofibers that are wavy and intertwined. This method is conducive to controlling the fiber diameter, crystallinity and internal molecular orientation, but its wavy and intertwined structure greatly affects the mechanical strength of the fiber. The electrospinning method can solve this problem. It can not only prepare continuous and uniform carbon nanofibers through two steps of stabilization and carbonization, but also adjust the fiber diameter and microstructure over a wide range. Polyacrylonitrile (PAN) can effectively complete the stabilization step and has a higher carbon yield due to the presence of periodic cyano substituents, so it is widely used as a precursor for preparing carbon nanofibers by electrospinning. At present, the main way to improve the mechanical properties of PAN-based carbon nanofibers is to optimize the type of spinning precursor polymer, electrospinning parameters, stabilization process, carbonization conditions, etc.

[0003] Designing precursor polymers is a strategy to achieve mechanical enhancement of carbon nanofibers from the source. For example: (1) Reference J. Solid State Electrochem. 2017, 22 (4), 1185 adds isopropyl titanate to the PAN / polyvinyl pyrrolidone spinning solution to obtain a TiC / C composite carbon nanofiber flexible film, and the fracture toughness of the fiber is improved by regulating the TiC content; (2) Authorized invention patent ZL201910174182.7 uses a mixed solution of PAN and lignin as a spinning solution, which can improve the mechanical strength of carbon nanofibers to a certain extent, but due to the poor compatibility of the two materials, the improvement is very limited; (3) Reference Cellulose 2020, 27 (7), 3789 uses a mixed solution of PAN and cellulose as a spinning solution, and improves the stabilization efficiency through the interaction between the two, thereby improving the mechanical strength of carbon nanofibers; (4) Reference Science 2019,366,1376–1379. Copolymerized methyl methacrylate-polyacrylonitrile was used as a precursor to prepare a nanofiber membrane by electrospinning. Polyethylene glycol bisazide was then used to cross-link the membrane by click chemistry reaction, and high-temperature pulling was performed to greatly improve the mechanical strength of the final carbon nanofiber membrane.

[0004] The electrospinning process can be regulated by changing the spinning solution concentration, spinning voltage, spinning rate, receiving method, etc., which can effectively control the fiber morphology, such as diameter, orientation, etc., but it does not have a direct impact on the final mechanical properties of carbon nanofibers.

[0005] The optimization of the stabilization process can be achieved by regulating the temperature and heating rate, for example: (1) The document Polym.Degrad.Stab.2012,97(8),1511 effectively regulates the mechanical properties of carbon nanofibers by changing the temperature and heating rate of the stabilization process; (2) The authorized invention patent ZL202010750233.9 and the document Adv.FiberMater.2021,3(1),14 effectively remove the residual solvent inside the PAN fiber by adding preheating treatment, thereby reducing the breakage of the fiber during the stabilization process and achieving a significant improvement in the mechanical strength of the carbon nanofiber membrane. In addition, the stabilization process can also be optimized by changing the structure of the precursor polymer, for example: (3) The document New Carbon Materials 2003,18(4),315 uses the copolymer of ionic group-containing itaconic acid and PAN as a precursor material to prepare carbon fibers, and uses itaconic acid to catalyze the stabilization step to obtain carbon nanofibers with better quality. (4) Reference Polymers 2019, 11(7), 1150 introduces 2-acrylamido-2-methyl-1-propanesulfonic acid containing ionic groups into PAN to reduce the activation energy of the cyclization reaction, promote the reaction, and improve the completeness of the stabilization process, thereby obtaining high-strength carbon nanofibers.

[0006] For the optimization of carbonization, the mechanical strength of carbon nanofibers can be improved by changing the carbonization temperature and heating rate. For example: (1) Reference Carbon 2010, 48 (1), 239 By increasing the carbonization temperature to 2800°C, the carbon nanofibers are further graphitized, and their structural regularity is much higher than that of carbon nanofibers conventionally carbonized at 1000°C, so their mechanical strength is greatly improved; (2) Reference Acta Polymerisca Sinica 2016, (6), 728 The results show that with the increase of the carbonization heating rate, the carbon content gradually increases. When the carbonization heating rate reaches 8K / min, the carbon content of the fiber reaches the highest 94.13%. The highly regular carbon structure improves its mechanical strength. (3) Reference Materials Letters, 2016, 183: 369-373 The carbon nanofibers are prepared by the carbonization pulling process, which effectively improves their mechanical strength. (4) Authorized invention patent CN113699694 introduces multi-walled carbon nanotubes into polyacrylonitrile nanofibers as microwave absorbing materials, heats the fibers to 800-1200°C by microwaves for carbonization, and prepares carbon nanofibers with a high carbonization rate.

[0007] Compared with the other three links, stabilization is an important intermediate process in the production of PAN-based carbon nanofibers, including many reactions such as cyclization and cracking, which has more advantages in improving the mechanical properties of carbon nanofibers. Among them, the cyclization reaction converts the linear PAN structure into a heat-resistant and stable cyclic structure, so that the PAN nanofiber can maintain a stable structure during the subsequent carbonization process. Therefore, cyclization is the key to the stabilization process and is very important for improving the mechanical properties of carbon nanofibers. However, traditional cyclization conditions will cause strong interactions and accumulation between cyano groups in PAN, resulting in heat accumulation in the reaction, and then a large amount of release, resulting in structural defects in the stabilized product. Although copolymers containing ionic groups can improve the cyclization reaction, the synthesis is difficult, the cost is high, and the copolymer performance is poor, which hinders the development of high-strength carbon nanofiber preparation technology. For the chemical regulation of this process, it usually involves structural changes in the precursor, which is currently achieved by direct modification of the precursor.

[0008] Since direct modification of the precursor is difficult and costly, and will significantly change its structure, the art urgently needs a new technology for modifying the nanofibers after spinning that is simple to operate and cost-effective, reduces the damage to the precursor structure, and achieves an efficient catalytic stabilization process to prepare high-strength carbon nanofibers. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing carbon nanofibers based on ionization pretreatment, which efficiently and simply introduces ionic groups into the initially spun PAN nanofibers, promotes carbon chain cyclization to form a stabilized structure, and thus improves the performance of the carbon nanofibers.

[0010] In order to achieve the above object, the present invention provides a method for preparing carbon nanofibers based on ionization pretreatment, comprising the following steps:

[0011] Step 1: dissolving polyacrylonitrile in a solvent under heating conditions, and obtaining a polyacrylonitrile spinning solution after standing and defoaming;

[0012] Step 2: electrospinning the polyacrylonitrile spinning solution obtained in step 1 to obtain a polyacrylonitrile nanofiber original membrane; in this step, the polyacrylonitrile nanofibers are uniformly deposited on the receiving roller by adjusting the process parameters, such as spinning voltage, solution propulsion speed, receiving distance, temperature and humidity, to obtain a polyacrylonitrile nanofiber original membrane;

[0013] Step 3: placing the original polyacrylonitrile nanofiber membrane obtained in step 2 in an alkaline aqueous solution for hydrolysis treatment, washing with acid and water in sequence, and drying at below 40° C. (preferably at room temperature) to obtain hydrolyzed polyacrylonitrile nanofibers;

[0014] Step 4: placing the hydrolyzed polyacrylonitrile nanofibers obtained in step 3 in a tubular furnace for stabilization heat treatment to obtain stabilized polyacrylonitrile nanofibers;

[0015] Step 5: The stabilized polyacrylonitrile nanofibers obtained in step 4 are placed in a tubular furnace and subjected to carbonization treatment under an inert gas atmosphere to obtain carbon nanofibers with enhanced mechanical properties.

[0016] Preferably, in step 1, the molecular weight of polyacrylonitrile is 100,000 to 200,000; the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and ethylene carbonate; and the mass fraction of the polyacrylonitrile spinning solution is 5 to 20 wt%.

[0017] Preferably, the process parameters of electrospinning in step 2 are: voltage 15-30 kV, solution propulsion speed 0.4-1.0 mL / h, receiving distance 15-25 cm, needle inner diameter 0.16-0.42 mm, relative humidity 35-85%, spinning temperature 22-26 ° C, receiving roller speed 100-400 rpm, spinning time 10-15 h.

[0018] Preferably, the alkaline aqueous solution in step 3 is at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide aqueous solutions.

[0019] Preferably, the concentration of the alkaline aqueous solution in step 3 is 0.1-6 mol / L, the time of the hydrolysis treatment is 0.5-10 h, and the temperature is 50-80° C.; the acid used is a hydrochloric acid aqueous solution with a pH of 1-6.

[0020] Preferably, the stabilization heat treatment in step 4 is carried out in an air atmosphere, and the conditions of the stabilization heat treatment are: heating rate 0.1-5°C / h, end point temperature 150-250°C, and holding time 0.5-2h.

[0021] Preferably, the inert gas in step 5 is argon or nitrogen, and the conditions of the carbonization treatment are: heating rate 1-20°C / h, end temperature 600-1500°C, and holding time 0.5-2h.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention adopts the method of introducing ionic groups by alkaline hydrolysis to modify PAN nanofibers in situ, thus avoiding structural damage caused by pretreatment of the precursor;

[0024] (2) The introduction of ionic groups through hydrolysis improves the efficiency of the stabilization process;

[0025] (3) Compared with the carbon nanofibers prepared by the traditional copolymerization and doping methods, the carbon nanofibers prepared by the present invention have higher mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of the preparation method provided by the present invention;

[0027] Figure 2 The X-ray photoelectron spectroscopy carbon fine spectrum of the PAN nanofibers obtained in step 3 of Example 1;

[0028] Figure 3 The stress-strain curves of the carbon nanofibers obtained in step 5 of Examples 1 to 3 and Comparative Example 1;

[0029] Figure 4 is the stress-strain curve of the carbon nanofiber obtained in step 5 of Example 4;

[0030] Figure 5 This is the stress-strain curve of the carbon nanofiber obtained in step 5 of Example 5. DETAILED DESCRIPTION

[0031] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.

[0032] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0033] Example 1

[0034] This embodiment provides a method for preparing carbon nanofibers based on ionization pretreatment. The preparation process is as follows: Figure 1 As shown, the following steps are included:

[0035] Step 1: Dissolve 15 g PAN in 85 g N,N-dimethylformamide and stir in a 60°C water bath for 6 h until PAN is completely dissolved, then let stand for 8 h to defoam.

[0036] Step 2: The spinning solution obtained in step 1 was subjected to electrospinning to prepare PAN nanofibers. The spinning parameters were as follows: spinning solution infusion rate 0.6 mL / h, voltage 24 kV, humidity 50%, temperature 25°C, spinning distance 17 cm, and roller speed 180 rpm.

[0037] Step 3: The PAN nanofibers were immersed in a 1 mol / L NaOH solution at 60° C. for 1 h for hydrolysis, and washed with a pH=3 hydrochloric acid solution and deionized water, and dried.

[0038] Step 4: Place the hydrolyzed PAN nanofibers in a tubular furnace, and heat them from room temperature to 220°C at a heating rate of 1°C / min in an air atmosphere. Keep the temperature for 1 hour to complete the stabilization process. When the furnace temperature drops to room temperature, take out the stabilized PAN carbon nanofibers for use.

[0039] Step 5: Place the stabilized PAN nanofibers in a tubular furnace, and heat the temperature from room temperature to 1000°C at a heating rate of 5°C / min in an argon atmosphere. Keep the temperature for 1 hour to complete the carbonization process. When the furnace temperature drops to room temperature, take out the carbonized carbon nanofibers.

[0040] Take part of the carbon nanofibers obtained in step 3 and perform X-ray photoelectron spectroscopy analysis. Figure 2 and measuring the stress-strain curve of the carbon nanofiber obtained in step 5, as shown Figure 3 shown.

[0041] Example 2

[0042] This embodiment provides a method for preparing carbon nanofibers based on ionization pretreatment. The preparation process is as follows: Figure 1 As shown, the following steps are included:

[0043] Step 1: Same as step 1 in Example 1.

[0044] Step 2: Same as step 2 in Example 1.

[0045] Step 3: Same as step 3 in Example 1, except that the soaking time is 2 h.

[0046] Step 4: Same as step 4 in Example 1.

[0047] Step 5: Same as step 5 in Example 1.

[0048] Example 3

[0049] This embodiment provides a method for preparing carbon nanofibers based on ionization pretreatment. The preparation process is as follows: Figure 1 As shown, the following steps are included:

[0050] Step 1: Same as step 1 in Example 1.

[0051] Step 2: Same as step 2 in Example 1.

[0052] Step 3: Same as step 3 in Example 1, except that the soaking time is 3 h.

[0053] Step 4: Same as step 4 in Example 1.

[0054] Step 5: Same as step 5 in Example 1.

[0055] Example 4

[0056] This embodiment provides a method for preparing carbon nanofibers based on ionization pretreatment. The preparation process is as follows: Figure 1 As shown, the following steps are included:

[0057] Step 1: Same as step 1 in Example 1.

[0058] Step 2: Same as step 2 in Example 1.

[0059] Step 3: Same as Step 3 in Example 1, except that the NaOH concentration is 2 mol / L.

[0060] Step 4: Same as step 4 in Example 1.

[0061] Step 5: Same as step 5 in Example 1, the stress-strain curve is as follows Figure 4 shown.

[0062] Example 5

[0063] This embodiment provides a method for preparing carbon nanofibers based on ionization pretreatment. The preparation process is as follows: Figure 1 As shown, the following steps are included:

[0064] Step 1: Same as step 1 in Example 1.

[0065] Step 2: Same as step 2 in Example 1.

[0066] Step 3: Same as Step 3 in Example 1, except that the soaking temperature is 80°C.

[0067] Step 4: Same as step 4 in Example 1.

[0068] Step 5: Same as step 5 in Example 1, the stress-strain curve is as follows Figure 5 shown.

[0069] Comparative Example 1

[0070] This embodiment provides a method for preparing carbon nanofibers, comprising the following steps:

[0071] Step 1: Same as step 1 in Example 1.

[0072] Step 2: Same as step 2 in Example 1.

[0073] Step 3: The same as step 3 in Example 1, except that clean water is used for soaking to complete the hydrolysis step.

[0074] Step 4: Same as step 4 in Example 1.

[0075] Step 5: Same as step 5 in Example 1.

[0076] like Figure 2 As shown in Figure 2, the peak of carboxylic acid appeared in the PAN nanofibers hydrolyzed by NaOH, proving that the hydrolysis successfully introduced carboxylic acid groups. Figure 3-5 As shown, by comparison, it can be seen that the mechanical strength of the carbon nanofibers of Examples 1-5 is greater than that of Comparative Example 1, wherein the mechanical strength of the carbon nanofibers prepared in Example 1 reaches 70.4 MPa, and the Young's modulus is 0.765 GPa.

[0077] The above description is only a preferred embodiment of the present invention and is not any formal or substantial limitation of the present invention. It should be pointed out that a person skilled in the art can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing carbon nanofibers based on ionization pretreatment, characterized in that: The following steps are involved: Step 1: dissolving polyacrylonitrile in a solvent under heating conditions, and obtaining a polyacrylonitrile spinning solution after standing and defoaming; Step 2: electrospinning the polyacrylonitrile spinning solution obtained in step 1 to obtain a polyacrylonitrile nanofiber original membrane; in this step, the polyacrylonitrile nanofibers are uniformly deposited on the receiving roller by adjusting the process parameters of spinning voltage, solution propulsion speed, receiving distance, and temperature and humidity to obtain a polyacrylonitrile nanofiber original membrane; Step 3: placing the polyacrylonitrile nanofiber original membrane obtained in step 2 in an alkaline aqueous solution for hydrolysis treatment, acid washing and water washing in sequence, and drying below 40° C. to obtain hydrolyzed polyacrylonitrile nanofibers; the alkaline aqueous solution is at least one of sodium hydroxide, potassium hydroxide, and calcium hydroxide aqueous solutions; the concentration of the alkaline aqueous solution is 0.1-6 mol / L, the hydrolysis treatment time is 0.5-10 h, and the temperature is 50-80° C.; Step 4: placing the hydrolyzed polyacrylonitrile nanofibers obtained in step 3 in a tubular furnace for stabilization heat treatment to obtain stabilized polyacrylonitrile nanofibers; Step 5: The stabilized polyacrylonitrile nanofibers obtained in step 4 are placed in a tubular furnace and subjected to carbonization treatment under an inert gas atmosphere to obtain carbon nanofibers with enhanced mechanical properties.

2. The preparation method according to claim 1, characterized in that In step 1, the molecular weight of polyacrylonitrile is 100,000-200,000; the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and ethylene carbonate; and the mass fraction of the polyacrylonitrile spinning solution is 5-20 wt%.

3. The preparation method according to claim 1, characterized in that The process parameters of the electrospinning in step 2 are: voltage 15~30 kV, solution propulsion speed 0.4~1.0 mL / h, receiving distance 15~25 cm, needle inner diameter 0.16~0.42 mm, relative humidity 35~85%, spinning temperature 22~26°C, receiving roller speed 100~400 rpm, and spinning time 10~15 h.

4. The preparation method according to claim 1, characterized in that: The acid washing adopts the hydrochloric acid aqueous solution with pH value of 1-6.

5. The preparation method according to claim 1, characterized in that: The stabilization heat treatment in step 4 is carried out in an air atmosphere, and the conditions of the stabilization heat treatment are: a heating rate of 0.1-5°C / h, an end point temperature of 150-250°C, and a holding time of 0.5-2h.

6. The preparation method according to claim 1, characterized in that: The inert gas in step 5 is argon or nitrogen, and the conditions of the carbonization treatment are: heating rate 1-20°C / h, end point temperature 600-1500°C, and holding time 0.5-2h.

Citation Information

Patent Citations

  • High-strength carbon nanofiber membrane and preparation method thereof

    CN112030353A

  • Method for preparing G / Sn / PAN-base carbon nanometer fiber membrane

    CN103757823A

  • Polyacrylonitrile nanofiber / polyimide-based carbon aerogel adsorption material and preparation method thereof

    CN105923622A

  • Method for preparing carbon nanofiber through electrostatic blending of polyacrylonitrile / lignin

    CN109943920A

  • Preparation method and application of nitrogen-doped porous carbon fiber material

    CN111235698A